UJI AKTIVITAS ANTIJAMUR EKSTRAK TERIPANG DARAH (Bohadschia argus) TERHADAP DAYA TAHAN JAMUR (Candida albicans) - Kurniawan, Nur Arif; Ibrahim, Ratna; Ridlo, Ali (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
The sintetic antifungal drugs in long term-use could have a side effects, so it isimportant to study natural drugs. B. argus is one of the natural resources that potential as anatural antifungal agent. The aimed of the research was to determine the antifungal activityof methanol, etil asetat and n-heksan extracts B. argus toward C. albicans and the effect ofthe different of B. argus toward the inhibitory zone of C. albicans and kind test substancescontained in of B. argus. The results showed that the B. argus extract contained of saponins,alkaloids and triterpenoids. The concentration (0 mg/ml, 15 mg/ml and 20 mg/ml) of extractof Bohadschia argus with methanol solvent resulted in significantly different inhibition.The concentration of 25 mg/ml was the best concentration with had medium categoryinhibitory zone (6.29 Â± 0.20mm) at against Candida albicans during 24 hours incubation.